Dualidad del CEO y comportamiento asimétrico de costos de operación - Bubeck, Stephan Klaus (2024)
Management decisions have an effect on cost behavior, and the duality of the CEO makes it easier for managers to make decisions based on personal interests. In Brazil, the Code of best corporate governance practices (Instituto Brasileiro de Governança Corporativa [IBGC], 2023) recommends that the chief executive officer (CEO) should not hold the position of chairman or member of the board of directors. In view of this, this research aimed to evaluate the effect of CEO duality on the asymmetric behavior of the operating costs (OC) of Brazilian publicly traded companies. To this end, descriptive, documentary and quantitative research was carried out on a balanced sample of 178 companies in the period 2012-2021, and the data was analyzed using descriptive statistics and hierarchical linear regression. This study adopted the perspective of Jensen and Meckling's agency theory (1976), in which managers make decisions based on personal interests. The results showed that companies with dual CEOs had a higher degree of asymmetry in operating costs during periods of falling sales than companies without dual CEOs. Thus, these results may be related to more aggressive operating cost reduction practices carried out by managers with duality during periods of falling sales.